2021
DOI: 10.1002/cbdv.202000964
|View full text |Cite
|
Sign up to set email alerts
|

Myrothins A–F from Endophytic Fungus Myrothecium sp. BS‐31 Harbored in Panax notoginseng

Abstract: Endophytic fungi play important roles for host's stress tolerance including invasion by pathogenic microbes. Small molecules are common weapons in the microbe–microbe interactions. Panax notoginseng is a widely used traditional Chinese medicinal plant and harbors many endophytes, some exert functions against pathogens. Here, we report six new compounds named myrothins A–F (1–6) produced by Myrothecium sp. BS‐31, an endophyte isolated from P. notoginseng, and their antifungal activities against pathogenic fungi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…Aided by single-crystal X-ray using CuK α radiation (CCDC-2121782, Figure 4), we clarified the absolute configuration of 2 as 4S,5R,8S,9S,10R,12S,16S and, accordingly, 2 was structurally elucidated unequivocally and named acrocalyene B. Through comparison of the present NMR spectra versus published data, the already-recognized compounds were elucidated respectively as agathic acid (3), [17] demethyl incisterol A 2 (4), [18] 23R-hydroxy-(20Z,24R)-ergosta-4,6,8 (14),20(22)-tetraen-3-one (5), [19] (22E,24S)-5,8-epidioxy-24-methylcholesta-6,9(11),22-trien-3-ol (6), [20] ganodermasides A (7) and B (8), [21] methyl dihydroferulate (9). [22] Cytotoxicity assessment was accomplished against such human carcinoma cells as RKO, HeLa and HCC-1806 for all the isolated compounds (Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Aided by single-crystal X-ray using CuK α radiation (CCDC-2121782, Figure 4), we clarified the absolute configuration of 2 as 4S,5R,8S,9S,10R,12S,16S and, accordingly, 2 was structurally elucidated unequivocally and named acrocalyene B. Through comparison of the present NMR spectra versus published data, the already-recognized compounds were elucidated respectively as agathic acid (3), [17] demethyl incisterol A 2 (4), [18] 23R-hydroxy-(20Z,24R)-ergosta-4,6,8 (14),20(22)-tetraen-3-one (5), [19] (22E,24S)-5,8-epidioxy-24-methylcholesta-6,9(11),22-trien-3-ol (6), [20] ganodermasides A (7) and B (8), [21] methyl dihydroferulate (9). [22] Cytotoxicity assessment was accomplished against such human carcinoma cells as RKO, HeLa and HCC-1806 for all the isolated compounds (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…They have intricate relations with host plants, which lead them to secrete secondary metabolites with novel skeleton and potent biologically active, and also to increase their adaptability to the survival stresses [2] . These fungi can produce terpenes, steroids, alkaloids and polyketides, which possess of cytotoxicity, anti‐inflammatory, neuroprotective, antibacterial and antifungal activities [3–7] …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The other six identified EF non-core genera were reported to have varied bioactivities. The endophytic Actinomucor, Penicillium, Nectria, Curvularia, Drechslera and Myrothecium were found to promote tolerance of their hosts against various types of stress [ 71 , 72 , 73 , 74 , 75 , 76 ]. As a whole, the role of the endophytism of EF in stress-tolerant species is worthy of future investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Xu et al [ 51 ] found the antifungal compound, falcarinol, from the endophytic fungus, a Paecilomyces sp., isolated from P. ginseng , and the fungus inhibited the fungal plant pathogen, Pyricularia oryzae , and four human pathogenic fungi. Xiong et al [ 52 ] found six novel compounds, named myrothins, from a Myrothecium endophyte isolated from P. notoginseng seedlings, which showed activity against the root rot fungi, F. oxysporum and Phoma herbarum . Ethyl acetate extracts of cell free filtrates of 40 endophytes from different tissues of P. ginseng were tested against six different fungal pathogens of ginseng, and the extracts of Colletotrichum pisi, F. oxysporum, F. solani, Phoma terrestris and two unidentified fungi showed antimicrobial activity against one or more of six ginseng fungal pathogens, except for C. destructans [ 53 ].…”
Section: Ginseng Interactions With Fungal Endophytesmentioning
confidence: 99%